Liquid cooling systems for individual cryotherapy units - Baranov, A.Yu.; Vasilenok, A.V.; Makarchuk, D.V.; Spiridonova, A.P. (Recent Contributions to Physics, 2022)
The use of liquid nitrogen in a cryoagent (LN) is a competitive advantage for individual cryotherapy units (IWBC). During the operation of this electric power industry, it is consumed only for auxiliary operations, since the heat load associated with the implementation of the technology of general cryotherapy (WBC) is covered by gasification of the cryoagent. An important, from a practical point of view, the advantage is that because of this IWBC devices consume no more than 1 kW of power and they can be connected to a household network, as well as create and operate mobile version IWBC installations. There is a widespread misconception that single-seat cryotherapy systems (cryosaunas) use liquid nitrogen irrationally. This opinion is based on the visual effects accompanying IWBC procedures and patients from the cockpit in the treatment room. Air flow of air in an air environment. Cryosauna manufacturers estimate the cost of a cryoagent for one IWBC capacity at 4.5 kg. In an advertisement for group WBC installations, manufacturers of such devices claim that LN costs do not exceed 100 kg/hour, given that the WBC received 50 people per hour, no more than 2 kg of LN is spent per patient. This is an advantage of the Nitrogen Refrigerated System (NCS) multi-seat units. Under the conditions of using a cryoagent in multi-site installations, it does not correspond to the heat fluxes entering the WBC zone, therefore the air temperature in them is unstable and during the procedures it rises by 50-60 K. The article provides a thermophysical analysis of the WBC process in cryosaunas.